Faktor Perilaku Hidup Tidak Sehat Terhadap Menopause Dini - Muri, Putri Hilwati (Universitas Aufa Royhan, 2023)
Early menopause is menopause that occurs at <40 years of age. In 75% of women vasomotor complaints have occurred, and in almost 50% of women osteoporosis has occurred. There are many causes that allow premature menopause to occur. The aim of this research is to analyze the influence of unhealthy lifestyle factors on early menopause. The research method used in this research is an analytical method with a cross sectional approach. The results of this research are the influence of irregular eating patterns on the incidence of early menopause, it is known that the probability value is 0.05 or more. is large with a probability value of Sig (0.05 > 0.000), so Ho is rejected and Ha is accepted, meaning that there is a significant influence between irregular eating patterns and early menopause. Conclusion: There is a significant influence between unhealthy lifestyle factors and early menopause. The suggestion of this research is to improve health behavior by avoiding bad habits that are detrimental to health and can cause premature menopause, such as irregular eating patterns, smoking, frequent anxiety/stress and taking herbal medicine/slimming medication.